A dose assessment method for nuclear facility decommissioning based on the combination of CAD and Point-Kernel method. (April 2022) - Liu, Yong-kuo; Chen, Zhi-tao; Chao, Nan; Peng, Min-jun; Jia, Ya-hui
Abstract: A gamma-ray dose assessment method based on the combination of Computer-Aided Design (CAD) and the Point-Kernel method is proposed in this paper. The proposed method is more adaptable to the dose assessment of scenes where the geometric model changes frequently. This approach introduces the Boolean operation function of the CAD models to meet the needs of frequent changes in the geometric model during the cutting and disassembly process. Moreover, ray tracing is performed based on the triangles on the surface of the model to calculate the mean free path, and finally, the point-kernel method is used to calculate the dose rate. Three sets of experiments are performed to demonstrate the Boolean modeling function and the accuracy of the dose calculation is verified. Compared with the existing methods, the method proposed in this paper can use the basic geometries of the model library to construct complex geometry through Boolean operations, and it can also read the CAD model and modify it online. Through the introduction of Boolean operations, CPKD realizes online construction and modification of CAD models, which facilitates geometric modeling and simplifies the processing flow of geometric changes during dose assessment. Highlights: This work presents an innovative dose assessment method based on CAD and point-kernel technique. The proposed method enable users to update the model geometry online through Boolean operations. The proposed method can perform dose assessment accurately and flexibly. The feasibility of the method is demonstrated in three different simulated decommissioning experiments.